2021
DOI: 10.3390/s21165526
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Surgery: How Do We Get to Autonomous Actions in Surgery?

Abstract: Most surgeons are skeptical as to the feasibility of autonomous actions in surgery. Interestingly, many examples of autonomous actions already exist and have been around for years. Since the beginning of this millennium, the field of artificial intelligence (AI) has grown exponentially with the development of machine learning (ML), deep learning (DL), computer vision (CV) and natural language processing (NLP). All of these facets of AI will be fundamental to the development of more autonomous actions in surger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 114 publications
(130 reference statements)
0
59
0
3
Order By: Relevance
“…Several studies have shown that robotic surgery is safe and feasible in the emergency setting. The main obstacle to its adoption is the lack of training and accessibility [15][16][17]. The current study clearly shows that trauma and acute care surgeons are enthusiasts and supportive of the use of AI in their clinical practice.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have shown that robotic surgery is safe and feasible in the emergency setting. The main obstacle to its adoption is the lack of training and accessibility [15][16][17]. The current study clearly shows that trauma and acute care surgeons are enthusiasts and supportive of the use of AI in their clinical practice.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have shown that robotic surgery is safe and feasible in the emergency setting. The main obstacle to its adoption is the lack of training and accessibility [ 15 17 ]. The current study clearly shows that trauma and acute care surgeons are enthusiasts and supportive of the use of AI in their clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although robots and computers may be able to effectively "see" through traditional concepts of CV such as instrument priors and motion analysis to create the third dimension, non-visual data points such as the interpretation of audio signals and light intensity readings may also be used. This review is a follow-up to a previously published article that, in addition to CV, also expanded upon the other pillars of AI such as machine learning (ML), deep learning (DP) and natural language processing as they pertain to autonomous actions in surgery [3].…”
Section: Introductionmentioning
confidence: 99%